Characterization of prepreg-prepreg and prepreg-tool friction for unidirectional carbon fiber/epoxy prepreg during hot diaphragm forming process. (April 2020) - Zhao, Yueqing; Zhang, Tao; Li, Hongfu; Zhang, Boming
Abstract: The frictional behaviors of prepreg-prepreg and prepreg-tool play the most important role in hot diaphragm forming and greatly influence the quality of the final product. A new set-up was developed to characterize the frictional behaviors for unidirectional carbon fiber/epoxy prepreg. The effects of temperature, normal force, pulling rate, and relative fiber angles on the frictional behaviors of the prepreg-prepreg and prepreg-tool interface have been investigated. Results of these tests are presented and observations are noted. The results show that the frictional resistance increases with increase in the normal force and the pulling rate, and its variation with the temperature is complicated. The frictional resistance is higher at 90° fiber orientation to the pulling direction than that at 45° and 0°. Highlights: A new apparatus was developed to characterize the friction for unidirectional carbon fiber/epoxy prepreg during hot diaphragm forming process. Inter-ply friction in-between prepreg and prepreg-tool frictional behavior were systematically investigated. The effect of temperature, normal force, and pulling rate on the frictional behavior of the prepreg-prepreg and prepreg-tool were studied. Measurements were performed with different relative fiber angles at the slipping interface. These results provide a large amount of data for subsequent simulation of diaphragm forming.